Alcohol use among medical students: a possible risk for future doctors? Uso de Álcool entre Estudantes de Medicina: um possível risco para futuros médicos? - Parente, Ezequiel Aguiar; Ferreira, Guilherme Emilio; Almeida, Beatriz de Cavalcante; de Alencar Filho, José Isnack Ponte; de Souza, Jessica Nascimento; Lima, Jose Wellington Oliveira; Almeida, Gilson Holanda (Journal of Health & Biological Sciences, 2017)
Introduction: The use of psychoactive drugs in the world population increased until 2011 as well the alcohol consumption of university students. Many studies have appointed factors that may aggravate the problem. Objective: To evaluate the alcohol use by medical students in a private medical institution in Fortaleza, Ceará. Methods: A quantitative, cross-sectional study developed from July of 2015 to May 2016. Two instruments for collecting data were used: one related to socioeconomic, demographic, and nosographic data; and the AUDIT, the most used instrument for evaluating alcohol disturbance. There were 502 students enrolled from the first to the eighth semester. The sample was composed by 384 students, representing 76.5% of the eligible population. Results: The prevalence of risk related to use of alcohol was 36%. 62% of the students were female; 61.9% single; the age average was 22 years. The AUDIT’s average score was 6.1 points. The majority of the students (64%) were classified as low risk use or abstinence (Zone I), while others 36% were located in different levels of risk. 37% had a positive family history for alcoholism, and only 28 (7.3%) had mental illness diagnosis. Variables as to being male, non-practicing religious, being sexually active, having a steady partner, concomitant use of tobacco and illicit drugs, living without the parents and hanging out with friends addicted to drinking were found to be risk factors for the abuse of alcohol. Conclusion: Data showed a high prevalence on the studied population in regard to risk related to the use of alcoholic beverages. The gravity of the problem demands health care and educational efforts to face it.